2006
DOI: 10.1097/00000542-200607000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Actions of Halothane and Sevoflurane on Spontaneous Ca2+Release in Rat Ventricular Myocytes

Abstract: Application of halothane and removal of sevoflurane sensitize the SR Ca(2+) release process (and vice versa on removal). Sevoflurane reversed the effects of halothane, suggesting they may act at the same subcellular target on the SR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Enflurane, halothane, and isoflurane concentrations exceeding MAC by an order of magnitude minimally affect Ca ++ channels in vitro 96,97. Halothane and sevoflurane exert opposite effects on Ca ++ release from sarcoplasmic reticulum,98 but are nearly exactly additive in their capacities to produce immobility 16. Knockout of the α IG T-type calcium channel does not alter MAC in mice 99.…”
Section: Relevance Of Plausible Specific Targets (Alphabetical Order)mentioning
confidence: 99%
“…Enflurane, halothane, and isoflurane concentrations exceeding MAC by an order of magnitude minimally affect Ca ++ channels in vitro 96,97. Halothane and sevoflurane exert opposite effects on Ca ++ release from sarcoplasmic reticulum,98 but are nearly exactly additive in their capacities to produce immobility 16. Knockout of the α IG T-type calcium channel does not alter MAC in mice 99.…”
Section: Relevance Of Plausible Specific Targets (Alphabetical Order)mentioning
confidence: 99%
“…Previous studies have also suggested that sevoflurane maintains SR Ca 2ϩ stores by blocking the spontaneous Ca 2ϩ release from the SR in rat ventricular myocytes. 49 It should be noted that sevoflurane exerts an inhibitory action on the plasma membrane Na ϩ /Ca 2ϩ exchanger 47 and Ca 2ϩ pump, 48 which could also result in Ca 2ϩ loading into the SR through the inhibition of Ca 2ϩ extrusion from the myocytes, 50 so long as there is sufficient adenosine 5Ј-triphosphate for SERCA-mediated SR Ca 2ϩ uptake. Because Ca 2ϩ depletion in the SR may act as an effective trigger for the activation of TRPC channels, [17][18][19] it is reasonable to propose that the better preservation of SR Ca 2ϩ levels by Postlong application of sevoflurane could result in less TRPC activation, and thereby contributes to a lower incidence of the Ca 2ϩ paradox, compared with Post application ( fig.…”
Section: Preservation Of Sr Ca 2؉ By Postlong Application Of Sevoflurmentioning
confidence: 99%
“…Importantly, in our cellular assay the mice were decapitated in the absence of anaesthesia because halothane has been described to alter calcium handling and increase spontaneous calcium release in rat ventricular myocytes (Graham et al . ), which could impair the cell isolation procedure and reduce cell viability and general health. After this, the heart was extracted and quickly immersed in a physiological saline solution, Cell Isolated Buffer (m m : 30 NaCl, 5.4 KCl, 0.5 MgCl 2 , 0.33 NaH 2 PO 4 , 25 Hepes and 22 glucose).…”
Section: Methodsmentioning
confidence: 99%